History of venereology in Croatia - Gruber, Franjo, liječnik (Array, 2009)
Summary: The term sexually transmitted infections has a wider meaning than the older venereal diseases. It is known that gonorrhea was present even in ancient times, whereas syphilis appeared in Europe at the end of the 15th century. Soon cases were observed along the coast in Zadar, Dubrovnik and Istria, and were treated by surgeons. The relatively late establishment of medical schools, along with wars and different governments, were some of the reasons why dermatovenereology as a specialty developed later in Croatia than in other European countries. Nevertheless, during the 19th century, many Croatian physicians and dermatovenereologists of the past century were interested in venereology. Among the most important personalities that worked at departments and dispensaries for venereal diseases were Cambieri, Kogoj, Božić, Nonveiller, Orhel, and many others. They introduced new diagnostic technologies and treatments, and wrote about these diseases. Significant progress was achieved in larger towns where medical schools had been opened. Croatian venereologists also organized several international congresses on sexually transmitted diseases and became members of the respective international societies. Nowadays, the interest of dermatovenereologists has been shifting towards chlamydial infections, herpes genitalis, human papillomavirus genital infection and human immunodeficiency virus infection, and their presence among homosexuals